An Investigation on Flexural Strengthening in Concrete Beam Using Woven Fabric Kenaf Composite Plates - Mohd Kamal, Ahmad Farhan; Ahmad, Hilton @ Mohd Hilton (Recent Trends in Civil Engineering and Built Environment, 2024)
Concrete beams are common structural elements in housing and bridge projects, primarily to carry flexural loads, necessitating a strengthening technique involving Fiber Reinforced Polymer (FRP) and the presence of kenaf composites manufacturing, which can replace synthetic composites in strengthening the flexural of beams, thereby expanding the applicability of green materials. The main aim for this research is to produce Kenaf Fiber Reinforced Polymer (KFRP) layer of plain-weave architectures as KFRP plates for flexural strengthening, conduct four-points bending test of normal concrete beam with variation of KFRP plate length and compare flexural strength of strengthened beam using KFRP plates with available synthetic composites materials. Twisted kenaf yarns were woven to exacting specifications, and epoxy glue was utilized to adhere the woven fabric kenaf plate to the concrete beam surface. A four-point bending test based on ASTM C78 standard was used to test the plain concrete beam strengthened with KFRP plate for this investigation. When compared to un-strengthened concrete beams (4.74 MPa), KFRP plate can improve flexural strengthening by up to 18% (5.28 MPa). However, this study found that when the length of the KFRP plate increases, concrete beams do not show increasing trends in flexural strengthening. The solution proposes that the woven fabric kenaf composites fabrication technology be improved by adopting automated manufacturing production for consistency, and that concrete beam mixing be done in a single batch to eliminate concrete strength variances.